DEVELOPING A CONCEPTUAL FRAMEWORK OF PANIC BUYING THROUGH CUSTOMERS’ EXPERIENCES DURING COVID19 PANDEMIC IN MALAYSIA: A QUALITATIVE APPROACH - Geoffrey Harvey Tanakinjal; Sharifah Nurafizah Syed Annuar; Shahiida Binti Musa (International Journal of Accounting, Finance and Business, 2022)
The coronavirus disease 2019 (COVID-19) has caused panic buying and is worthy of consideration due to the rapid spread of the emerging pandemic. People across cultures and national borders have raided shops at every point of the outbreak. Malaysia's fast-moving consumer goods firms have faced intensified pressure to raise production to meet demand. Limited research in consumer behaviour theory has dealt with this collective act of panic buying or, in other words, of stockpiling. To understand this collective action by consumers in a crisis situation from store operators' view, a framework needs to be developed from panic literature. This paper aims to explore the factors that explain consumers' panic buying at the emergence of COVID-19 and investigate buying patterns that may benefit store operators and the supply chain. The present study will be conducted using a qualitative approach, which aims to investigate and describe changes in consumer buying behaviour during a health crisis. Focus group and individual interviews gather insights into the memory's view by retail store operators of customer panic purchases of daily needs and other supplies in more detail and context relevant to the study. These groups are not fully representative of the entire target population but could provide some level of generalisation for the cities in Malaysia. A framework of panic buying consisting of factors derived from the qualitative analysis will be developed from these data which will also provide a general pattern of items or products bought from stores involved. This research can provide essential results for understanding how consumers can spontaneously purchase something. The framework thus developed from this research may make it easier to make economic choices in relative social isolation.